Associations of drinking water and urinary uranium with incident diabetes among U.S. adults: The Multi-Ethnic Study of Atherosclerosis and the Strong Heart Family Study - Maya Spaur; Kathrin Schilling; Ronald A. Glabonjat; Anirban Basu; Kevin P. Patterson; Wil Lieberman-Cribbin; Qixuan Chen; Filippo Ravalli; Marta Galvez-Fernandez; Pam Factor-Litvak; Steven Chillrud; Benjamin C. Bostick; et al. (Environmental Research, 2026)

Effect of dissolved versus total zinc levels on bacterial zinc-dependent meropenem co-resistance in River Tyne sediments - Catherine L. Hands; Sonia Gupta; Anke Neumann; Charles W. Knapp; S.Z. Ahammad; Jason Snape; David W. Graham (Environmental Pollution, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A subduction-modified source for the parental melts to MARID assemblages from the Kaapvaal craton lithosphere and their formation via hybridisation with wall-rock peridotite - Jason C. Hinde; Philip E. Janney; Hélène Legros; Yan Luo; Sarah Woodland; Graham D. Pearson (Mineralogy and Petrology, 2025)

Improved trace element discrimination of kimberlitic and carbonatitic zircon: implications for zircon origin in kimberlite and the search for superdeep diamonds - Matthew F. Hardman; D. Graham Pearson; S. Andy DuFrane; Izaac Cabral-Neto; Rogério G. Azzone; Qiao Shu; Jason Hinde; Alexei S. Rukhlov (Mineralogy and Petrology, 2025)

Effect of a cognitive behavioural therapy intervention to improve sleep on food preferences: A randomized controlled trial in adults with overweight and obesity - Ayan M. Merchant; Stuart R. Gray; Cindy M. Gray; Graham Finlayson; Anthony M. Manyara; Maria F. Gabler Trisotti; Jason M.R. Gill (Appetite, 2025)

Reduction of postharvest fungal spoilage of tomato fruit using bacterial antagonists - Hailey R. Graham; Jonathan Ononiwu; Sydney Massine; Jason Lafontaine; Tyler J. Avis (Journal of Plant Pathology, 2025)

Future climate projections in the global coastal ocean - Jason Holt; Anna Katavouta; Joanne Hopkins; Laurent O. Amoudry; Christian M. Appendini; Lars Arneborg; Alex Arnold; Yuri Artioli; Jerome Aucan; Barbara Berx; Laura Cagigal; Michela De Dominicis; et al. (Progress in Oceanography, 2025)

Remote sensing of electron precipitation mechanisms enabled by ELFIN mission operations and ADCS - Ethan Tsai; Akhil Palla; Austin Norris; James King; Cindy Russell; Sophie Ye; Jiashu Wu; Jason Mao; Sharvani Jha; Chanel Young; Graham Wing; Kevin Lian; et al. (Advances in Space Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Hemisphere- and condition-specific alpha oscillations support semantic and spatial cognition in aging - Maggie P. Rempe; Danae S. Manta; Kayle Cohen; Ryan J. Glesinger; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Lucy K. Horne; Grant M. Garrison; Kennedy A. Kress; Lucas Weyrich; Chloe C. Casagrande; et al. (GeroScience, 2025)

Evolution of novel Mesorhizobium genospecies that competitively and effectively nodulate Cicer arietinum following inoculation with the Australian commercial inoculant strain M. ciceri CC1192 - Yvette J. Hill; MacLean G. Kohlmeier; Alireza Agha Amiri; Graham W. O’Hara; Jason J. Terpolilli (Plant and Soil, 2025)
Background and aims Mesorhizobium ciceri CC1192 is the commercial inoculant strain for Cicer arietinum (chickpea) cultivation in Australia, including in the Ord River Irrigation Area (ORIA), where C. arietinum cropping began in 1985. Mesorhizobium strains are known to gain the capacity to nodulate legumes through acquisition of symbiosis Integrative and Conjugative Elements (ICEs), leading to the evolution of novel rhizobia. Here, we assess the impact of symbiosis ICE transfer and compare the genomic diversity and symbiotic effectiveness of C. arietinum nodulating rhizobia from the ORIA. Methods Nodule isolates collected from field cultivated C. arietinum were genotyped by RAPD-PCR, and representative strains from each genotype were whole genome sequenced and symbiotically phenotyped in glasshouse conditions to assess N 2 fixation effectiveness against CC1192. Results A total of 68 nodule isolates, all harbouring the CC1192 symbiosis ICE (ICE Mc Sym 1192 ), were analysed, with 12 identified as the inoculant strain, and 56 novel strains clustering into ten genotypes. These novel genotypes dominated as nodule occupants across the majority of sites sampled. Nine of the ten representative strains were as effective at N 2 fixation as CC1192, with WSM4904 the only ineffective strain. Core genome phylogeny showed the ten strains represent four novel Mesorhizobium genospecies. Novel strains WSM4904 and WSM4906 shared 98.7% sequence identity, yet exhibited very different symbiotic phenotypes. Conclusions The CC1192 symbiosis ICE has transferred to a wide diversity of Mesorhizobium spp. in the ORIA. These evolved strains are competitive against CC1192 at nodulating C. arietinum , and the majority are effective symbiotic N 2 fixers.

Is sexual size dimorphism in walleye, Sander vitreus , a driver of seasonal movements in Lake Erie? - Christian J. Bihun; Matthew D. Faust; Richard T. Kraus; Thomas M. MacDougall; Jason M. Robinson; Christopher S. Vandergoot; Graham D. Raby (Journal of Fish Biology, 2025)
Walleye ( Sander vitreus ) are a sexually dimorphic species in which females are larger than males in adulthood. Walleye can also exhibit sex‐ and population‐based differences in migration behavior. In Lake Erie, we used acoustic telemetry to test the prediction that female walleye exhibit larger broad‐scale movements than males during the summer and autumn. This prediction was based on the hypothesis that greater foraging in females would be needed to satisfy their higher energy requirements. We quantified movements of males and females from distinct spawning populations from Lake Erie's west and east basins using a lake‐wide grid of acoustic receivers in 2017 and 2018. We found no differences between male and female home range sizes, core range sizes, or distances travelled in either population. Fish length‐at‐tagging was unrelated to the size of a fish's home range or to its distance travelled, contrary to previous predictions about body size as a driver of migration distance in the Lake Erie population. We found that west basin walleye occupied large and indiscrete portions of the lake, but the core range of females extended into the central basin, whereas males were concentrated in the west basin. Walleye originating from the east basin confined their movements primarily to the east basin and showed stronger home range overlap among members of their population than did walleye from the west basin population. Within either population, walleye had more home range overlap with members of the same sex, which likely reflects differences in the migratory tendencies of males and females.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Estimating the Importance of Viral Contributions to Soil Carbon Dynamics - Amy E. Zimmerman; Emily B. Graham; Jason McDermott; Kirsten S. Hofmockel (Global Change Biology, 2024)
Biogeochemical models for predicting carbon dynamics increasingly include microbial processes, reflecting the importance of microorganisms in regulating the movement of carbon between soils and the atmosphere. Soil viruses can redirect carbon among various chemical pools, indicating a need for quantification and development soil carbon models that explicitly represent viral dynamics. In this opinion, we derive a global estimate of carbon potentially released from microbial biomass by viral infections in soils and synthesize a quantitative soil carbon budget from existing literature that explicitly includes viral impacts. We then adapt known mechanisms by which viruses influence carbon cycles in marine ecosystems into a soil‐explicit framework. Finally, we explore the diversity of virus–host interactions during infection and conceptualize how infection mode may impact soil carbon fate. Our synthesis highlights key knowledge gaps hindering the incorporation of viruses into soil carbon cycling research and generates specific hypotheses to test in the pursuit of better quantifying microbial dynamics that explain ecosystem‐scale carbon fluxes. The importance of identifying critical drivers behind soil carbon dynamics, including these elusive but likely pervasive viral mechanisms of carbon redistribution, becomes more pressing with climate change.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Prediction of solar energetic events impacting space weather conditions - Manolis K. Georgoulis; Stephanie L. Yardley; Jordan A. Guerra; Sophie A. Murray; Azim Ahmadzadeh; Anastasios Anastasiadis; Rafal Angryk; Berkay Aydin; Dipankar Banerjee; Graham Barnes; Alessandro Bemporad; Federico Benvenuto; et al. (Advances in Space Research, 2024)

Using multi-platform LiDAR to guide the conservation of the world's largest temperate woodland - Tommaso Jucker; Carl R. Gosper; Georg Wiehl; Paul B. Yeoh; Nat Raisbeck-Brown; Fabian Jörg Fischer; Jason Graham; Helen Langley; William Newchurch; Alison J. O'Donnell; Gerald F.M. Page; Katherine Zdunic; et al. (Remote Sensing of Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Simultaneous detection of SARS-CoV-2, influenza A, respiratory syncytial virus, and measles in wastewater by multiplex RT-qPCR - Emalie K. Hayes; Madison T. Gouthro; Jason J. LeBlanc; Graham A. Gagnon (Science of The Total Environment, 2023)

Widespread distribution of honey bee-associated pathogens in native bees and wasps: Trends in pathogen prevalence and co-occurrence - Kaitlin R. Deutsch; Jason R. Graham; Humberto F. Boncristiani; Tomas Bustamante; Ashley N. Mortensen; Daniel R. Schmehl; Ashlyn E. Wedde; Dawn L. Lopez; Jay D. Evans; James D. Ellis (Journal of Invertebrate Pathology, 2023)

Competition in the Phaseolus vulgaris-Rhizobium symbiosis and the role of resident soil rhizobia in determining the outcomes of inoculation - George M. Mwenda; Yvette J. Hill; Graham W. O’Hara; Wayne G. Reeve; John G. Howieson; Jason J. Terpolilli (Plant and Soil, 2023)
Background and Aims Inoculation of legumes with effective N 2 -fixing rhizobia is a common practice to improve farming profitability and sustainability. To succeed, inoculant rhizobia must overcome competition for nodulation by resident soil rhizobia that fix N 2 ineffectively. In Kenya, where Phaseolus vulgaris (common bean) is inoculated with highly effective Rhizobium tropici CIAT899 from Colombia, response to inoculation is low, possibly due to competition from ineffective resident soil rhizobia. Here, we evaluate the competitiveness of CIAT899 against diverse rhizobia isolated from cultivated Kenyan P. vulgaris . Methods The ability of 28 Kenyan P. vulgaris strains to nodulate this host when co-inoculated with CIAT899 was assessed. Rhizosphere competence of a subset of strains and the ability of seed inoculated CIAT899 to nodulate P. vulgaris when sown into soil with pre-existing populations of rhizobia was analyzed. Results Competitiveness varied widely, with only 27% of the test strains more competitive than CIAT899 at nodulating P. vulgaris . While competitiveness did not correlate with symbiotic effectiveness, five strains were competitive against CIAT899 and symbiotically effective. In contrast, rhizosphere competence strongly correlated with competitiveness. Soil rhizobia had a position-dependent numerical advantage, outcompeting seed-inoculated CIAT899 for nodulation of P. vulgaris, unless the resident strain was poorly competitive. Conclusion Suboptimally effective rhizobia can outcompete CIAT899 for nodulation of P. vulgaris . If these strains are widespread in Kenyan soils, they may largely explain the poor response to inoculation. The five competitive and effective strains characterized here are candidates for inoculant development and may prove better adapted to Kenyan conditions than CIAT899.

Impact of acute consumption of beverages containing plant-based or alternative sweetener blends on postprandial appetite, food intake, metabolism, and gastro-intestinal symptoms: Results of the SWEET beverages trial - Eva Almiron-Roig; Santiago Navas-Carretero; Gabriele Castelnuovo; Louise Kjølbæk; Ana Romo-Hualde; Mie Normand; Niamh Maloney; Charlotte A. Hardman; Charo E. Hodgkins; Hariklia Moshoyiannis; Graham Finlayson; Corey Scott; et al. (Appetite, 2023)

Demand reduction and energy saving potential of thermal energy storage integrated heat pumps - Jason Hirschey; Zhenning Li; Kyle R. Gluesenkamp; Tim J. LaClair; Samuel Graham (International Journal of Refrigeration, 2023)

Correction to: Partial body cryotherapy exposure drives acute redistribution of circulating lymphocytes: preliminary findings - Catriona L. Rose; Helen McGuire; Kenneth Graham; Jason Siegler; Barbara Fazekas de St Groth; Corinne Caillaud; Kate M. Edwards (European Journal of Applied Physiology, 2023)

Partial body cryotherapy exposure drives acute redistribution of circulating lymphocytes: preliminary findings - Catriona L. Rose; Helen McGuire; Kenneth Graham; Jason Siegler; Barbara Fazekas de St Groth; Corinne Caillaud; Kate M. Edwards (European Journal of Applied Physiology, 2023)
Partial body cryotherapy (PBC) is proposed to alleviate symptoms of exercise-induced muscle damage (EIMD) by reducing associated inflammation. No studies have assessed acute PBC exposure on peripheral blood mononuclear cell mobilisation or compared these with cold water immersion (CWI), which may inform how PBC impacts inflammatory processes. This trial examined the impact of a single PBC exposure on circulating peripheral blood mononuclear cells compared to CWI or a control. 26 males were randomised into either PBC (3 min at − 110 to − 140 °C), CWI (3 min at 9 °C), or control (3 min at 24 °C), with blood samples, heart rate, and blood pressure taken before and after exposure. Cytometric analysis determined that CD8 + T-cell populations were significantly elevated after treatments, with PBC increasing CD8 + T cells to a greater degree than either CWI or CON. Natural killer cell counts were also elevated after PBC, with the increase attributed specifically to the CD56 lo CD16 + cytotoxic subset. This provides the first evidence for the effect of PBC exposure on redistribution of immune cells. An increase in circulating leukocyte subsets such as CD8 + T cells and CD56 lo CD16 + natural killer cells suggests that PBC may induce a transient mobilisation of lymphocytes. PBC may thus enable a more efficient trafficking of these cells from the circulation to the site of initial cellular insult from exercise, potentially accelerating the process of cellular recovery. This provides novel evidence on the use of PBC as a recovery treatment and may also have applicability in other clinical settings involving the recovery of damaged skeletal muscle.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Phytoplankton and cyanobacteria abundances in mid‐21st century lakes depend strongly on future land use and climate projections - Karan Kakouei; Benjamin M. Kraemer; Orlane Anneville; Laurence Carvalho; Heidrun Feuchtmayr; Jennifer L. Graham; Scott Higgins; Francesco Pomati; Lars G. Rudstam; Jason D. Stockwell; Stephen J. Thackeray; Michael J. Vanni; et al. (Global Change Biology, 2021)
Land use and climate change are anticipated to affect phytoplankton of lakes worldwide. The effects will depend on the magnitude of projected land use and climate changes and lake sensitivity to these factors. We used random forests fit with long‐term (1971–2016) phytoplankton and cyanobacteria abundance time series, climate observations (1971–2016), and upstream catchment land use (global Clumondo models for the year 2000) data from 14 European and 15 North American lakes basins. We projected future phytoplankton and cyanobacteria abundance in the 29 focal lake basins and 1567 lakes across focal regions based on three land use (sustainability, middle of the road, and regional rivalry) and two climate (RCP 2.6 and 8.5) scenarios to mid‐21st century. On average, lakes are expected to have higher phytoplankton and cyanobacteria due to increases in both urban land use and temperature, and decreases in forest habitat. However, the relative importance of land use and climate effects varied substantially among regions and lakes. Accounting for land use and climate changes in a combined way based on extensive data allowed us to identify urbanization as the major driver of phytoplankton development in lakes located in urban areas, and climate as major driver in lakes located in remote areas where past and future land use changes were minimal. For approximately one‐third of the studied lakes, both drivers were relatively important. The results of this large scale study suggest the best approaches for mitigating the effects of human activity on lake phytoplankton and cyanobacteria will depend strongly on lake sensitivity to long‐term change and the magnitude of projected land use and climate changes at a given location. Our quantitative analyses suggest local management measures should focus on retaining nutrients in urban landscapes to prevent nutrient pollution from exacerbating ongoing changes to lake ecosystems from climate change.

Age and growth of early‐life‐stage Atlantic tarpon ( Megalops atlanticus) from the northcentral Gulf of Mexico - Patrick M. Graham; James S. Franks; Evan J. Anderson; Robert T. Leaf; Jason D. Tilley (Journal of Fish Biology, 2021)
Age and growth of early‐life‐stage Atlantic tarpon Megalops atlanticus collected from Mississippi coastal waters in the northcentral Gulf of Mexico (GOM) are described using otolith microstructure analysis. Tarpon leptocephali ( n = 95, 16.0—27.8 mm standard length, L S ) collected from June throughOctober 2013—2018, ranged in age from 22 to 43 days (mean = 30.9 ± 0.5 days). Leptocephalus somatic growth rates ranged 0.46—1.24 mm day −1 (mean = 0.76 ± 0.02 mm day −1 ), and leptocephalus otolith growth rates ranged 1.78—3.97 μm day −1 (mean = 2.58 ± 0.04 μm day −1 ). Growth rates were inversely correlated to leptocephalus age, indicating the shrinkage phase associated with leptocephalus metamorphosis. Juvenile tarpon ( n = 358, 50—359 mm fork length, L F ) were collected from August through December 2007—2018. Juveniles exhibited a positive allometric relationship (adjusted R 2 = 0.99, P L F ) ranged from 76 to 174 days. Juvenile growth rate was estimated as 1.56 ± 0.11 mm day −1 . Significant ( P R 2 = 0.81) and radius ( R 2 = 0.68). Evaluation of the backcalculated hatch dates suggests that specimens in the collection hatched from late May through mid‐September with slight peaks during July and August. A Rao's Spacing Test of Uniformity indicates the presence of significant lunar periodicity in leptocephalus hatch dates ( n = 95, U = 250.1, P

The extent and variability of storm‐induced temperature changes in lakes measured with long‐term and high‐frequency data - Jonathan P. Doubek; Orlane Anneville; Gaël Dur; Aleksandra M. Lewandowska; Vijay P. Patil; James A. Rusak; Nico Salmaso; Christian Torsten Seltmann; Dietmar Straile; Pablo Urrutia‐Cordero; Patrick Venail; Rita Adrian; et al. (Limnology and Oceanography, 2021)
The intensity and frequency of storms are projected to increase in many regions of the world because of climate change. Storms can alter environmental conditions in many ecosystems. In lakes and reservoirs, storms can reduce epilimnetic temperatures from wind‐induced mixing with colder hypolimnetic waters, direct precipitation to the lake's surface, and watershed runoff. We analyzed 18 long‐term and high‐frequency lake datasets from 11 countries to assess the magnitude of wind‐ vs. rainstorm‐induced changes in epilimnetic temperature. We found small day‐to‐day epilimnetic temperature decreases in response to strong wind and heavy rain during stratified conditions. Day‐to‐day epilimnetic temperature decreased, on average, by 0.28°C during the strongest windstorms (storm mean daily wind speed among lakes: 6.7 ± 2.7 m s −1 , 1 SD) and by 0.15°C after the heaviest rainstorms (storm mean daily rainfall: 21.3 ± 9.0 mm). The largest decreases in epilimnetic temperature were observed ≥2 d after sustained strong wind or heavy rain (top 5 th percentile of wind and rain events for each lake) in shallow and medium‐depth lakes. The smallest decreases occurred in deep lakes. Epilimnetic temperature change from windstorms, but not rainstorms, was negatively correlated with maximum lake depth. However, even the largest storm‐induced mean epilimnetic temperature decreases were typically

Responder Needs Addressed by Arctic Maritime Oil Spill Modeling - Jessica Manning; Megan Verfaillie; Christopher Barker; Catherine Berg; Amy MacFadyen; Michael Donnellan; Mark Everett; Clifton Graham; Jason Roe; Nancy Kinner (Journal of Marine Science and Engineering, 2021)
There is a greater probability of more frequent and/or larger oil spills in the Arctic region due to increased maritime shipping and natural resource development. Accordingly, there is an increasing need for effective spilled-oil computer modeling to help emergency oil spill response decision makers, especially in waters where sea ice is present. The National Oceanic & Atmospheric Administration (NOAA) Office of Response & Restoration (OR&R) provides scientific support to the U.S. Coast Guard Federal On-Scene Coordinator (FOSC) during oil spill response. OR&R’s modeling products must provide adequate spill trajectory predictions so that response efforts minimize economic, cultural, and ecologic impacts, including those to species, habitats, and food supplies. The Coastal Response Research Center is conducting a project entitled Oil Spill Modeling for Improved Response to Arctic Maritime Spills: The Path Forward, in conjunction with modelers, responders, and researchers. A goal of the project is to prioritize new investments in model and tool development to improve response effectiveness in the Arctic. The project delineated FOSC needs during Arctic maritime spill response and provided a solution communicating sources of uncertainty in model outputs using a Confidence Estimates of Oil Model Inputs and Outputs (CEOMIO) table. The table shows the level of confidence (high, medium, low) in a model’s trajectory prediction over scenario-specific time intervals and the contribution of different component inputs (e.g., temperature, wind, ice) to that result.

Mismatch repair gene pathogenic germline variants in a population-based cohort of breast cancer - Tu Nguyen-Dumont; Jason A. Steen; Ingrid Winship; Daniel J. Park; Bernard J. Pope; Fleur Hammet; Maryam Mahmoodi; Helen Tsimiklis; Derrick Theys; Mark Clendenning; Graham G. Giles; John L. Hopper; et al. (Familial Cancer, 2020)

Review of Australian east coast low pressure systems and associated extremes - Andrew J. Dowdy; Acacia Pepler; Alejandro Di Luca; Leone Cavicchia; Graham Mills; Jason P. Evans; Simon Louis; Kathleen L. McInnes; Kevin Walsh (Climate Dynamics, 2019)

Cultures of Gossypium barbadense cotton ovules offer insights into the microtubule-mediated control of fiber cell expansion - Ethan T. Pierce; Benjamin P. Graham; Michael R. Stiff; Jason A. Osborne; Candace H. Haigler (Planta, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Archipelagic genetics in a widespread Caribbean anole - R. Graham Reynolds; Tanner R. Strickland; Jason J. Kolbe; Bryan G. Falk; Gad Perry; Liam J. Revell; Jonathan B. Losos (Journal of Biogeography, 2017)
Aim We examine the influence of fluctuating sea levels in a land‐bridge archipelago on the apportioning of intraspecific genetic diversity and divergence in the widespread Puerto Rican crested anole ( Anolis cristatellus ). We compare three alternative scenarios for genetic diversification in an archipelagic species that contrast the relative influences of periodic isolation versus island connectedness driven by fluctuating sea levels. Our approach combines information from geography and population genetics to assess the influence of island size, island isolation, island historical geography, and population genetic processes such as drift on the contemporary distribution of genetic variation within and among islands. Location The Puerto Rico Bank in the Caribbean focusing primarily on the Spanish, British and U.S. Virgin Islands. Methods We used nuclear and mitochondrial DNA sequences and microsatellite genotypes sampled from A. cristatellus populations to investigate: (1) the broad‐scale pattern of phylogeographical divergence across Puerto Rico Bank islands and (2) diversification within the Virgin Islands archipelago. For the first component, we used sequence data to reconstruct the relationships among 542 samples from across the species range. For the second component, we examined the relative influences of island size, isolation, and population genetic processes on the distribution of genetic diversity across the Virgin Islands. Results In the Virgin Islands, A. cristatellus is represented by a monophyletic clade except on the island of Vieques, where two divergent clades coexist. We found evidence for non‐equilibrium dynamics in the Virgin Islands, suggesting spatial population expansion during intraglacial periods of low sea level. Main conclusions We found limited evidence that periods of island isolation affected patterns of genetic diversity and differentiation. Instead, we found that the patterns of genetic diversity and divergence in A. cristatellus in the Virgin Islands archipelago are likely shaped by long‐term persistence in the region and periods of population spatial expansion.

Miocene extensional tectonics explain ancient patterns of diversification among turret‐building tarantulas ( Aphonopelma mojave group) in the Mojave and Sonoran deserts - Matthew R. Graham; Brent E. Hendrixson; Chris A. Hamilton; Jason E. Bond (Journal of Biogeography, 2015)
Aim Phylogeographical studies in the Mojave and Sonoran deserts often find genetic discontinuities that pre‐date the Pleistocene. A recent synthesis of phylogeographical data, called the Mojave Assembly Model, provides a hypothesis for the historical assembly of these desert biotas but does not adequately capture the complexity of pre‐Pleistocene vicariance events. We tested this model and assessed pre‐Pleistocene divergences by exploring the phylogeography of the Aphonopelma mojave group, which is composed of turret‐building tarantula species from the Mojave and Sonoran deserts. Location Mojave and Sonoran deserts, south‐western USA . Methods We augmented the sampling from a previous study by sequencing mitochondrial DNA ( COI ) from new material of the A. mojave group. We used phylogenetic and network analyses to identify clades and a molecular clock and lineages‐through‐time plots ( LTT plots) to explore the timing and tempo of diversification. We tested for demographic expansion using neutrality tests and mismatch distributions. Species distribution models ( SDM s) were constructed to compare current suitable habitat to that at the Last Glacial Maximum ( LGM ). Results Phylogenetic, network and molecular‐clock analyses identified six major clades that probably diverged during the late Miocene. The rate of diversification appears to have slowed during the Pliocene. Most clades exhibit signals of recent demographic expansion. SDM s predicted that suitable habitat shifted south and to lower elevations during the LGM . Main conclusions Phylogeographical analyses suggest that the A. mojave group experienced a burst of diversification in the late Miocene, followed by population expansions during the Pleistocene. Six major clades with origins in the late Miocene cannot be adequately explained by the Mojave Assembly Model. We propose the novel hypothesis that Miocene extensional tectonics caused populations to diverge in allopatry by producing low‐elevation habitat barriers. Geological models, such as kinematic reconstructions, provide an ideal but underutilized framework for testing biogeographical hypotheses in these deserts and the wider Basin and Range Province.

Life history of harbor porpoises ( Phocoena phocoena ) in Scottish ( UK ) waters - Jennifer A. Learmonth; Sinead Murphy; Patricia L. Luque; Robert J. Reid; I. Anthony P. Patterson; Andrew Brownlow; Harry M. Ross; Jason P. Barley; M. Begoña Santos; Graham J. Pierce (Marine Mammal Science, 2014)
Life history parameters were determined for stranded and bycaught harbor porpoises ( Phocoena phocoena ) from Scottish ( UK ) waters (1992–2005). Fetal growth rate was 84.4 mm/mo and mean size at birth was 76.4 cm (range 65–88 cm). Males and females had a similar range of body lengths (65–170 cm and 66–173 cm, respectively), although asymptotic lengths were higher in females than males (approximately 158 cm and 147 cm, respectively). Nonpregnant females were significantly lighter, in relation to their length than males. Maximum estimated age was 20 yr for both sexes. Age at sexual maturity ( ASM ) was estimated as 4.35 yr in females and 5.00 yr in males. Conception occurred mainly in July and August although reproductively active males were recorded during April to July. Gestation lasted 10–11 mo, with calving mainly between May and July. Lactating females were recorded during June to November, while small calves with solid food in their stomachs were found mainly during February to May. Estimated pregnancy rate (0.34–0.40) is lower than recorded elsewhere, but is likely underestimated due to the prevalence of mature females of poor health status in the sample. Nevertheless, cetacean strandings can be an essential source of data on demographic parameters.

Protection against peroxynitrite-induced DNA damage by mesalamine: implications for anti-inflammation and anti-cancer activity - Paul M. Graham; Jason Z. Li; Xueging Dou; Hong Zhu; Hara P. Misra; Zhenquan Jia; Yunbo Li (Molecular and Cellular Biochemistry, 2013)

Comparative mapping in watermelon [Citrullus lanatus (Thunb.) Matsum. et Nakai] - Katherine Sandlin; Jason Prothro; Adam Heesacker; Nelly Khalilian; Rebecca Okashah; Wenwen Xiang; Eleni Bachlava; David G. Caldwell; Chris A. Taylor; Danelle K. Seymour; Victoria White; Eva Chan; et al. (Theoretical and Applied Genetics, 2012)

Conserved anchorless surface proteins as group A streptococcal vaccine candidates - Anna Henningham; Emiliano Chiarot; Christine M. Gillen; Jason N. Cole; Manfred Rohde; Marcus Fulde; Vidiya Ramachandran; Amanda J. Cork; Jon Hartas; Graham Magor; Steven P. Djordjevic; Stuart J. Cordwell; et al. (Journal of Molecular Medicine, 2012)

Stable isotope analysis in two sympatric populations of bottlenose dolphins Tursiops truncatus: evidence of resource partitioning? - Ruth Fernández; Susana García-Tiscar; M. Begoña Santos; Alfredo López; Jose A. Martínez-Cedeira; Jason Newton; Graham J. Pierce (Marine Biology, 2011)

Hydrological and biogeochemical controls on the timing and magnitude of nitrous oxide flux across an agricultural landscape - MICHAEL J. CASTELLANO; JOHN P. SCHMIDT; JASON P. KAYE; CHARLES WALKER; CHRIS B. GRAHAM; HENRY LIN; CURTIS J. DELL (Global Change Biology, 2010)
Anticipated increases in precipitation intensity due to climate change may affect hydrological controls on soil N 2 O fluxes, resulting in a feedback between climate change and soil greenhouse gas emissions. We evaluated soil hydrologic controls on N 2 O emissions during experimental water table fluctuations in large, intact soil columns amended with 100 kg ha −1 KNO 3 ‐N. Soil columns were collected from three landscape positions that vary in hydrological and biogeochemical properties ( N = 12 columns). We flooded columns from bottom to surface to simulate water table fluctuations that are typical for this site, and expected to increase given future climate change scenarios. After the soil was saturated to the surface, we allowed the columns to drain freely while monitoring volumetric soil water content, matric potential and N 2 O emissions over 96 h. Across all landscape positions and replicate soil columns, there was a positive linear relationship between total soil N and the log of cumulative N 2 O emissions ( r 2 = 0.47; P = 0.013). Within individual soil columns, N 2 O flux was a Gaussian function of water‐filled pore space (WFPS) during drainage (mean r 2 = 0.90). However, instantaneous maximum N 2 O flux rates did not occur at a consistent WFPS, ranging from 63% to 98% WFPS across landscape positions and replicate soil columns. In contrast, instantaneous maximum N 2 O flux rates occurred within a narrow range (−1.88 to −4.48 kPa) of soil matric potential that approximated field capacity. The relatively consistent relationship between maximum N 2 O flux rates and matric potential indicates that water filled pore size is an important factor affecting soil N 2 O fluxes. These data demonstrate that matric potential is the strongest predictor of the timing of N 2 O fluxes across soils that differ in texture, structure and bulk density.

Disaster vulnerability and evacuation readiness: coastal mobile home residents in Florida - Margarethe Kusenbach; Jason L. Simms; Graham A. Tobin (Natural Hazards, 2010)

Hydrologic and biotic influences on nitrate removal in a subtropical spring‐fed river - James B. Heffernan; Matthew J. Cohen; Thomas K. Frazer; Ray G. Thomas; Travis J. Rayfield; Jason Gulley; Jonathan B. Martin; Joseph J. Delfino; Wendy D. Graham (Limnology and Oceanography, 2010)
We use a long‐term chemical and hydrologic record in combination with longitudinal sampling and high‐frequency nitrate (NO 3 ‐ ) measurements from in situ sensors to describe temporal and spatial patterns of nitrogen (N) inputs and removal in the spring‐fed Ichetucknee River (Columbia County, Florida) and to determine the hydrological, geomorphic, and biological factors that influence those dynamics. Over a 20‐yr period of record, NO 3 ‐N removal averaged 118 kg N d ‐1 (0.77 g N m ‐2 d ‐1 ) over the upper 5 km of the Ichetucknee River. Three independent estimates of gross autotrophicNassimilation (from gross primary production, diel NO 3 ‐ variation, and standing biomass) agreed closely but accounted for less than 20% of observed N removal. Longitudinal surveys indicate negligible or negative dissolved organic nitrogen and ammonium (NH 4 + ) production, suggesting that denitrification is the predominant mechanism of N removal in this river. A positive relationship between discharge and the magnitude of NO 3 ‐N removal shows that interactions with the surrounding floodplain exert considerable influence at high flows, and longitudinal NO 3 ‐ patterns indicate that N removal may be influenced by channel morphology. These results suggest a greater role for dissimilatory processes and hydrologic connectivity with hyporheic and floodplain sediments than has been previously recognized in highly productive spring‐fed rivers of north Florida. While hydrologic variation is the primary determinant of variation in NO 3 ‐ removal within the Ichetucknee River, comparison across systems indicates that biotic characteristics can cause significant deviation from predictions based on purely physical models of relationships between river size and N removal.

Stable carbon and nitrogen isotope ratio profiling of sperm whale teeth reveals ontogenetic movements and trophic ecology - Sónia Mendes; Jason Newton; Robert J. Reid; Alain F. Zuur; Graham J. Pierce (Oecologia, 2007)

Ferroplasma cupricumulans sp. nov., a novel moderately thermophilic, acidophilic archaeon isolated from an industrial-scale chalcocite bioleach heap - Rebecca B. Hawkes; Peter D. Franzmann; Graham O’hara; Jason J. Plumb (Extremophiles, 2006)

Osteopontin Knockdown Suppresses Tumorigenicity of Human Metastatic Breast Carcinoma, MDA-MB-435 - Lalita A. Shevde; Rajeev S. Samant; Jason C. Paik; Brandon J. Metge; Ann F. Chambers; Graham Casey; Andra R. Frost; Danny R. Welch (Clinical & Experimental Metastasis, 2006)

Sugarcane biotechnology: The challenges and opportunities - Prakash Lakshmanan; R. Jason Geijskes; Karen S. Aitken; Christopher L. P. Grof; Graham D. Bonnett; Grant R. Smith (In Vitro Cellular & Developmental Biology - Plant, 2005)